Selective Catalytic Oxidation of Benzyl Alcohol to Benzaldehyde by Nitrates - Xu, Shurui; Wu, Jie; Huang, Peng; Lao, Chunwen; Lai, Hanchao; Wang, Yuxiong; Wang, Zhenyu; Zhong, Guoyu; Fu, Xiaobo; Peng, Feng (Frontiers in Chemistry, 2020)
In this paper, the ferric nitrate was used to oxidize the benzyl alcohol in a mild condition. Comparing with HNO3, ferric nitrate exhibited an excellent activity in the benzyl alcohol oxidation. The conversion and product selectivity could be both as high as 95% in N2 atmosphere and the benzaldehyde yield also reached 85% in air. Similar to Fe(NO3)3·9H2O, the other metallic nitrates such as Al(NO3)3·9H2O and Cu(NO3)2·3H2O could also oxidize the benzyl alcohol. As an effective oxidant, the applicability of Fe(NO3)3·9H2O for other benzylic alcohol was also investigated and the reaction condition was optimized at the same time. The results showed the Fe(NO3)3·9H2O would be more conducive to oxidize benzyl alcohol in anaerobic condition. The experiments in N2 and O2 atmospheres were designed to study the catalytic mechanism of Fe(NO3)3. The results showed the combination of Fe3+ and NO3- had high activity while either one was with negligible oxidation ability. The cyclic transformation of Fe3+ and Fe2+ provided the catalytic action for the benzyl alcohol oxidation. The role of NO3- was an oxidant by providing HNO2 in anaerobic condition while NO3- could be regenerated from NO in aerobic condition. Though O2 was not beneficial for the benzyl alcohol conversion directly, it could eliminate the unwelcome NO and simultaneously reinforce the circulation between Fe2+ and Fe3+, forming a green cyclic oxidation process. Hence, the benzyl alcohol oxidation was suggested in air atmosphere for efficient and the need of green synthesis.